Role-Based Stress and Burnout among Nigerian Sample: The Moderating Role of Self-Efficacy - Ugwu, Cynthia C.; Okonkwo, Ejike A.; Ngwoke, Celestine I. (International Journal of Social and Administrative Sciences, 2020)
There has been much research linking role-based stress to burnout among nurses, but there has been little effort to study the moderating role of self-efficacy in this link in the Nigerian nurses. Considering the theoretical assumptions of the job demand-resources model linking role-based stress and self-efficacy to burnout, this cross-sectional study investigated the moderating role of self-efficacy in role-based and burnout relations among nurses in Enugu urban area of Enugu State, Nigeria. One hundred and seventy (170) nurses, comprising 43 males and 127 females between the ages of 22 to 55 years were sampled using multi-stage sampling techniques. The 15-item Job Tension Scale, 22-item Burnout Inventory and 10-item Generalized Self-efficacy Scale were administered for data collection. Results of moderated regression analysis revealed that role-based stress and emotional self-efficacy did not equally predict the components of burnout. Self-efficacy positively moderated only feeling of reduced personal accomplishment component of burnout. Role-based stress and self-efficacy accounted for 3.1% of the variance in emotional exhaustion of the nurses, 11.8 % of variance in dehumanization and 35.3% in feeling of reduced personal accomplishment. Specifically, role-based stress independently and positively predicted feeling of reduced personal accomplishment but not emotional exhaustion and dehumanization. Self-efficacy independently and negatively predicted emotional exhaustion, dehumanization and feeling of reduced personal accomplishment. The study has recommended that policy makers in nursing/health sector should reduce role-based stress while enhancing self-efficacy in order to reduce burnout.